The Effectiveness of the Newborn Care Education Program on the Anxiety of Primiparadi Mothers at Tengku Peukan Regional General Hospital, Southwest Aceh Regency - Cut Lola Mutia; Agustina; Aasnaini; Yusdiana; Ari Wahyuni (Journal Public Health and Clinical Science, 2026)
The neonatal period is the most critical phase of a baby's life, so it requires optimal care. Primipara mothers often experience anxiety in caring for newborns due to a lack of knowledge and experience. This condition can affect the quality of baby care and the success of the mother's adaptation process in carrying out her new role. Therefore, interventions in the form of educational programs are needed to increase knowledge and reduce maternal anxiety. To determine the effectiveness of the newborn care education program on maternal anxiety at the Tengku Peukan Regional General Hospital, Southwest Aceh Regency. This study is a quantitative research with a cross-sectional design. Data collection was carried out from February to March 2026. The population in this study was all mothers who had 54 newborns, with a sampling technique using total sampling. The research instrument used a questionnaire on the level of anxiety of primipara mothers. Data analysis was carried out univariate and bivariate using the Wilcoxon Signed Rank Test. The results showed that before being educated, most mothers experienced mild anxiety (53.70%) and moderate anxiety (24.07%). After being educated, there was a decrease in anxiety with the majority of respondents in the categories of not anxious (51.85%) and mild anxiety (33.33%). The results of the Wilcoxon test showed a p-value of 0.000 (p < 0.05) which means there is a significant difference. Conclusion: The newborn care education program is effective in reducing the anxiety level of primitive mothers at Tengku Peukan Hospital. Suggestion: It is hoped that health workers can increase the provision of education on newborn care systematically and continuously as part of postnatal services to increase maternal readiness in caring for babies.